2005
DOI: 10.1016/j.femsyr.2004.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Point mutation in calcium-binding domain of mouse polyomavirus VP1 protein does not prevent virus-like particle formation, but changes VP1 interactions with cell structures

Abstract: The mouse polyomavirus gene for the major structural protein, VP1, with point mutation in the calcium-binding pocket (VP1(Ala)), was expressed in Saccharomyces cerevisiae and in a baculovirus expression system. Surprisingly, VP1(Ala) forms virus-like particles (VLPs) in nuclei of both yeast and insect cells. VP1(Ala)-VLPs produced in S. cerevisiae are unstable and, unlike wild-type VP1 (VP1(wt))-VLPs, they disassemble during the purification procedure and storage. In contrast to VP1(wt), VP1(Ala) does not inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The removal of Ca 2ϩ from capsids could be particularly crucial for viruses that depend on metal ions for assembly and stability, such as rotavirus, mouse polyomavirus, and dragon grouper nervous necrosis virus (DGNNV) (1,39,43). A few studies have reported that mutations at the metal-binding sites decrease virus infectivity by impairing the early stages of virus-host interaction and genome release (23,24).…”
Section: Divalent Metal Ions Are Components Of Numerous Icosahedral Vmentioning
confidence: 99%
“…The removal of Ca 2ϩ from capsids could be particularly crucial for viruses that depend on metal ions for assembly and stability, such as rotavirus, mouse polyomavirus, and dragon grouper nervous necrosis virus (DGNNV) (1,39,43). A few studies have reported that mutations at the metal-binding sites decrease virus infectivity by impairing the early stages of virus-host interaction and genome release (23,24).…”
Section: Divalent Metal Ions Are Components Of Numerous Icosahedral Vmentioning
confidence: 99%
“…VLP samples were suspended in buffer with bromophenol blue and 10% v/v glycerol (final concentration) to aid loading. EDTA was avoided in buffers as polyomavirus VLPs are known to be stabilized by interactions with calcium ions. , Nucleic acid staining was performed by soaking the gel in 1× GelRed (Biotium #41003) in TA buffer for 1 h at room temperature, with gentle shaking. 0.5 μg of DNA ladder (Thermo Scientific #SM0311) was loaded as a positive control.…”
Section: Methodsmentioning
confidence: 99%
“…VLP samples were suspended in buffer with bromophenol blue and 10% v/v glycerol (final concentration) to aid loading. EDTA was avoided in buffers as polyomavirus VLPs are known to be stabilised by interactions with calcium ions 30,55 . Nucleic acid staining was performed by soaking the gel in 1X GelRed (Biotium #41003) in TA buffer for 1 hour at room temperature, with gentle shaking.…”
Section: Methodsmentioning
confidence: 99%